The impact of replacing breakfast grains with meat/meat alternatives: an evaluation of child nutrition policy - Hanson, Jennifer A; Cantrell, Olivia; Paez, Paola; Brenes, Priscilla; Laursen, Denise E (Public health nutrition, 2020)
To evaluate the Child and Adult Care Food Program (CACFP) rule that allows a meat/meat alternative to replace the breakfast grain requirement three times per week. A 5-week menu including breakfast, lunch and snack was developed with meat/meat alternative replacing the breakfast grain requirement three times per week. Menu nutrients based on the minimum requirements were compared with reference values representing the Acceptable Macronutrient Distribution Range for fat and a range of reference values representing two-thirds the Dietary Reference Intake for 3-year-olds and 4-5-year-olds. The meal pattern minimum requirements were compared with two-thirds of those recommended by the Dietary Guidelines for Americans (DGA). Evaluation took place between April and June 2019. Human subjects were not utilized. The CACFP minimum grain requirement is well below the DGA reference value (0·5-1·5 v. 3·33 ounce-equivalents). Energy (2208·52 kJ) was below the reference values (3126·83-4362·53 kJ). Protein (34·43 g) was above the reference values (9·87-10·81 g). Carbohydrate (76·65 g), fibre (7·46 g) and vitamin E (1·69 mg) were below their reference values of 86·67 g, 10·46-14·60 g and 4-4·76 mg, respectively. Fat (22·57 %) was below the reference range (25-40 %). The CACFP rule which allows a meat/meat alternative to replace the breakfast grain requirement three times per week may result in meal patterns low in energy, carbohydrate, fat, fibre and vitamin E, while providing an excessive amount of protein.